Bibliometic Insights Into Agriculture And Artisanal Mining In Rural Communities - Sununianti, Vieronica; Nugroho, Heru (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Agriculture has become the focus of rural communities’ livelihood, alongside artisanal mining. This study analyzes previous literature both three. The bibliometric method and VOSviewer software were used to analyze metadata from the Scopus database which the publication pattern tends to increase. Galvin Hilson is the most influential, prolific, and cited. The United Kingdom and the United States produced the most documents and had the highest citations. There are correlation between country, journal, and dominanttopic. This article is limited to the Scopus database until early 2023. Further studies are recommended to micro topics on other types of artisanal mining in the global south.